Cryptic speciation in the Lesser Elaenia Elaenia chiriquensis (Aves: Passeriformes: Tyrannidae) - Rheindt, Frank E.; Krabbe, Niels; Wee, Alison K.s.; Christidis, Les (Zootaxa, 2015)
Tyrant-flycatchers (Tyrannidae) are a taxonomically confusing bird group containing a large degree of cryptic diversity that has only recently begun to be unraveled through the application of acoustic and molecular methods. We investigated all three subspecies of the Lesser Elaenia, Elaenia chiriquensis Lawrence, across their range using sound recordings as well as nuclear and mitochondrial markers. We show that two of the three subspecies, the nominate race from southern Central America and the widespread South American subspecies E. c. albivertex Pelzeln, have undergone very low levels of vocal and molecular differentiation across their fragmented range. In contrast, the isolated taxon E. c. brachyptera Berlepsch, endemic to the western and also, as recently shown, eastern slopes of the northern Andes, is phylogenetically and vocally distinct from other Lesser Elaenias, indicating that it constitutes a separate biological species.